(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The research was aimed to know the effect of aqueous and alcoholic extracts of Allium porrum on some hematological parameters of male rats (n=35). Rats were divided into groups and were administrated different concentrations (200, 400, and 800) mg/kg of extract daily for one week to study the parameters of hematological parameters compared to control group. The treatment with A. porrum extracts led to increasing RBC and P.C.V. for all extract concentrations and to both kinds. The aqueous extract 800 mg/kg shows more significant effect than the other levels. A significant increase in hemoglobin concentration for aqueous extract 800 mg/kg and 400 mg/kg and alcoholic extract 800 mg/kg and alcoholic extract 800 mg/kg were more significant than the other levels and a significant decrease in WBC count for alcoholic extract 400 mg/kg compared to the control group.